PRELIMINARY STUDY OF POLLUTION BY AIR ASBESTOS IN THE CENTER OF LIMA - Acero Rosales, Tomás (2003)
We had studied the pollution in downtown of Lima by asbest, partícles and dust. The particles with asbest, are emited to the atmosphere from brake of car. These particles have bad eflect in the heallh of people (give asbestosis), who aro working in downtown of Lima (Av. Abancay)